Selection and characterization of Bacillus thuringiensis strains toxic against pyralid stored‐product pests. (8th January 2015) - Azzouz, H.; Kebaili‐Ghribi, J.; Daoud, F.; Abdelmalak, N.; Ennouri, K.; Belguith‐Ben Hassan, N.; Tounsi, S.; Rouis, S.
Abstract In this study, we present the selection and the characterization of Bacillus thuringiensis strains toxic against pyralid pests of stored products. Among 201 new B. thuringiensis strains isolated from different countries, two strains (BLB249 and BLB384) showed greater toxicity than the commercialized strain B. thuringiensis kurstaki HD1 against Ephestia kuehniella larvae. Morphological, molecular and biochemical investigations revealed that these strains were similar to HD1 but presented different cry gene content. Additional bioassays revealed that only strain BLB249 displayed higher toxicity than HD1 against Plodia interpunctella larvae. The study of Cry protoxin activation by midgut proteases of E. kuehniella and P. interpunctella larvae supported that higher toxicity of BLB249 and BLB384 strains compared to HD1 was not due to differential protoxin activation. Moreover, the toxic strains produced δ‐endotoxins and spores in similar amounts to HD1. Interestingly, the δ‐endotoxin production and the yield of BUPM26 strain were 32.87% and 35.12% greater than that of HD1. The potent insecticidal activities of BLB249 and BLB384 strains and the high level of δ‐endotoxin production by BUPM26 strain make them excellent candidates for use against E. kuehniella and P. interpunctella larvae.